Role of socioeconomic status on the prevalence of low-birth-weight babies in allied hospital Faisalabad - Iftikhar, Aysha; Ashraf, Afifa; Waheed, Aniqa; Payam, Ahada (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the impact of socioeconomic status on the prevalence of low birth weight babies. Method: The cross-sectional study was conducted at the Allied Hospital, Faisalabad, Pakistan, from March 28, 2022, to February 28, 2023, and comprised mothers with low birthweight infants (<2500g). Data included maternal age, residential status, educational status of the parents, prenatal care practices, maternal workload, infection incidence during pregnancy, relevant family history, maternal weight, income level, employment status, and drug usage. Data was analysed using SAS 9.4. Results: Of the 120 mothers with mean age 30.5+/-6.1 years, 90(75%) were aged 18-40 years, 78(65%) resided in rural areas, and 82(68%) had lower educational levels. Moreover, 80(67%) mothers did not receive antenatal care, and 44(37%) reported infections during pregnancy. Family history of low birthweight babies was prevalent in 64(53.33%) cases. Maternal weight was normal in 78(65%) cases. The income level was less than Pak Rupee 10,000 in 88(73.33%) cases and there were 90(75%) non-working women. Overall, 81(67.5%) of the infants developed postnatal jaundice. Conclusion: A complex interplay of socioeconomic factors, including maternal age, family income, occupation, area of residence, education level and antenatal care utilisation, was evident in relation to low birthweight. Key Words: Low birth weight infants, Socioeconomic factors, Family income, Education, Antenatal care visits, Maternal health services.